INOVASI PEMBELAJARAN HOLISTIK PAI DI ERA KURIKULUM MERDEKA UNTUK MENGEMBANGKAN KECERDASAN EMOSIONAL SISWA - Jimmy Malintang; Nurul Laely Mahmudah; Saidatul Munazilah; Fahmi; Ahmad Hadi Pranoto; Alhijir Yasir Abdul Karim (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Islamic Religious Education (IRE) learning in the era of the Independent Curriculum is required to not only focus on cognitive aspects, but also to be able to develop students' emotional intelligence as preparation for facing the challenges of the 21st century. This study aims to formulate a holistic PAI learning innovation model that is relevant to emotional resilience needs. A descriptive qualitative research approach was used through library research by reviewing national and international literature on PAI, emotional intelligence, and the Merdeka Curriculum. Data analysis was conducted using content analysis techniques to identify conceptual relationships and opportunities for integration. The results showed that a holistic approach based on reflection, empathy, collaboration, and social projects was effective in developing five aspects of emotional intelligence: self-awareness, self-management, motivation, empathy, and social skills. This study confirms that this model makes PAI not only a means of knowledge transfer, but also a transformative medium for shaping the character, spirituality, and emotional resilience of students. Thus, holistic PAI learning innovation within the framework of the Merdeka Curriculum has the potential to strengthen the function of Islamic education as a pillar of developing a superior, adaptive, and noble generation.